Application of the Herbal Mineral Block to Support Goat Farming Business Productivity in Salit Village, Karo Regency - patriani, peni patriani (Journal of Saintech Transfer, 2023)
Harapan Maju is a farmer group in the goat farming business in Salit Village, Karo Regency, North Sumatra Province. The livestock business is carried out semi-intensively by utilizing agricultural waste as feed. The problems faced by the Harapan Maju Farmer Group are a decrease in goat productivity, low body weight, less optimal management of livestock feed, and environmental pollution conditions due to agricultural waste. The solution to the problem is to apply nutritional supplement technology (Herbal Mineral Block) to livestock and feed preparation from agricultural waste. The methods used in community service are extension, training and practice, and mentoring. The results of community service activities are 1) improved science and technology skills in increasing goat productivity through feed preparation; 2) improved skills of farmers in making nutritional supplements (Herbal Mineral Block); 3) reduced pollution from agricultural waste; 4) increased goat productivity through feed using agricultural waste; 5) increased income through the improvement of goat farming business managemen